Distance Learning in Focus: A Bibliometric and Thematic Network Analysis of the Global Research Trends - Abantas, Jeannie C.; Akmad, Sabrie E.; Bonggat Jr., Rogelio B.; Abubakar, Al-jayson U.; Nuruddin, Nahdiyya H.; Hajan, Bonjovi H.; Ayangco-Derramas, Clarissa; Jr., Jovito C. Anito (International Journal of Learning, Teaching and Educational Research, 2025)
The COVID-19 pandemic has reshaped the global educational landscape, accelerating the adoption of distance learning and influencing teaching and learning in the post-pandemic context. This bibliometric and thematic network analysis has examined the research landscape of distance learning during the pandemic. Using a predefined search syntax in the Scopus® database, with publication years limited to 2018–2023 and language restricted to English, 14,525 research documents were retrieved for analysis. Bibliometric assessments of research production, temporal and spatial trends, impact, and collaboration were conducted using Excel and VOSViewer. Additionally, SciMAT was employed to visualize thematic density, centrality, and evolution through strategic diagrams, evolution maps, and stability maps. The findings indicate that distance learning research is predominantly conducted in Western nations, with the United States leading in publication output. The most common subject areas include social sciences, computer sciences, and engineering. The study also highlights significant methodological and theoretical interconnectedness, emphasizing the expansion of virtual and flexible learning environments. Furthermore, it underscores the growing role of virtual education, the gendered impact of online learning, and the increasing intersection of educational technology and academic performance. By mapping the conceptual evolution of distance education research, this study provides a strategic foundation for future investigations and policy development to enhance global distance learning frameworks. https://doi.org/10.26803/ijlter.24.4.34